Comparative Analysis of User Experience between Teachers and Students on Vocational School E-learning using UEQ+ - I Made Lanang Putra Pringgadhana; Rian Permana Yatmika Putra; Hagi Semara Putera; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (ISB Atma Luhur, 2026)
The rapid digital transformation in the Industry 4.0 era has increased the adoption of e-learning systems in vocational education, making user experience (UX) evaluation essential. Previous studies have mainly focused on student’s perspectives, while teachers UX remain underexplored. This study aims to compare the UX perceptions of teachers and students toward the e-learning system at SMK TI Bali Global Jimbaran using the User Experience Questionnaire Plus (UEQ+). A quantitative approach was employed involving 74 students and 17 teachers who had used the system for at least one year. Seven UEQ+ dimensions were analyzed, and differences were tested using the Wilcoxon Signed Rank Test. The result show that teachers rated attractiveness, intuitive use, visual aesthetics, content quality and content trustworthiness positively (mean scores >1.0). Efficiency was rated moderately (M=0.21), while social interaction received a very low score (M=-1.34). Students rated most dimensions as fair to good (mean scores around 0.5-1.0), whereas efficiency and visual aesthetics were considered acceptable but requiring improvement. Social interaction was evaluated as neutral to slightly negative. These findings demonstrate significant difference in UX perceptions and highlight the need for improved interaction features and system performance in vocational e-learning systems.